2002
DOI: 10.1097/00007632-200209150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Purely Epidural Spinal Meningioma Mimicking Metastatic Tumor

Abstract: Extradural spinal meningiomas may mimic metastatic disease. Attention needs to be drawn to this dangerous preoperative and intraoperative misinterpretation, which may easily entail an inadequate therapy. Intraoperative histology is mandatory for optimal surgical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…In the 17 case reports reviewed, 11 patients had total resections, 1 patient died for unclear reasons (18), 1 patient had a recurrence 13 years after the initial complete tumor removal (4), and 1 patient improved but did not completely recover from the initial neurological deficit (7). One case report did not present follow-up data (12), and the rest of the cited series reported that patients were asymptomatic at their most recent follow-up exam (2,4,9,11,19). In cases of subtotal resection, 1 author did not provide follow up information (17), 2 patients died (4,20), 2 patients had paresis (2), and 1 patient developed paraplegia (2).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 17 case reports reviewed, 11 patients had total resections, 1 patient died for unclear reasons (18), 1 patient had a recurrence 13 years after the initial complete tumor removal (4), and 1 patient improved but did not completely recover from the initial neurological deficit (7). One case report did not present follow-up data (12), and the rest of the cited series reported that patients were asymptomatic at their most recent follow-up exam (2,4,9,11,19). In cases of subtotal resection, 1 author did not provide follow up information (17), 2 patients died (4,20), 2 patients had paresis (2), and 1 patient developed paraplegia (2).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Extradural lesions are most commonly metastatic neoplasms (1). The literature reports the occurrence of extradural meningioma as 2.7 to 10% of spinal neoplasms (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), occurring most commonly in the thoracic spine (3,4,8,10,13).…”
Section: Introductionmentioning
confidence: 99%
“…[2] They may have an extradural component in approximately 10% of cases; but an exclusively extradural meningioma is an uncommon entity. [5] This entity assumes significance in the context that extradural spinal lesions are most commonly metastatic neoplasms (including lymphoma), and hence, the correct intraoperative identification is indispensible for instituting the correct treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The majority of spinal meningiomas are entirely intradural and <10% show an extradural component. [5] Meningiomas located purely in the extradural space are exceedingly rare and, therefore, are seldom considered in the differential diagnosis of spinal extradural lesions. [5] We present two cases of totally extradural en plaque meningiomas of the spine, which posed significant intraoperative dilemma as to the nature of the pathology and the treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Multiple myeloma, chordoma, Ewing sarcoma and chondrosarcoma are the common primary malignancies; hemangioma, giant cell tumor, eosinophilic granuloma and osteochondroma are the usual benign tumors seen at this location. 14 Meningioma is usually not a primary clinical consideration when an extradural spinal lesion is identified.…”
Section: Discussionmentioning
confidence: 99%